VISIBLE SPECTROPHOTOMETRIC METHODS FOR THE QUANTITATIVE ESTIMATION OF LOPINAVIR IN THEIR FORMULATIONS - V.Nagalakshmi; K.Sreelatha; NVNB SrinivasaRao; N.Gayatri Devi; K.Swarnalatha; M.Rama; C.A.Jyothirmayee; N.Madhavi; K.J.Subhashishini; A.Nirmala Jyothna (International Journal of Innovations in Engineering Research and Technology, 2023)
Simple, accurate and reproducible UV-Visible spectrophotometric methods were established for the assay of LOP based on the substitution and condensation reactions. Condensation the LOP with Xanthydrol/H2SO4 is proposed in method A. Method B includes substitution of LOP with chloranilic acid . The optical characteristics such as Beers law limits, molar absorptivity and Sandell’s sensitivity for the methods (A-B) are given. Regression analysis using the method of least squares was made to evaluate the slope(b), intercept(a) and correlation coefficient (r) and standard error of estimation (Se) for each system.Determination of LOP in bulk form and in pharmaceutical formulations were also incorporated